2020
DOI: 10.11591/ijpeds.v11.i3.pp1211-1219
|View full text |Cite
|
Sign up to set email alerts
|

Effect analysis of residual magnetism availability level on the success of voltage generation processes in self-excited induction generators

Abstract: The voltage generation process is a very crucial initial stage for the successful operation of the self-excited induction generator (SEIG). The availability of residual magnetism and the adequacy of excitation capacitor value are factors that determine the success of the voltage generation process on the SEIG. This paper analyzes the effect of the availability of residual magnetism on the rotor's magnetic core. With a simple approach, the terminal voltage on the SEIG can be solved through the intersect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It has been shown that the magnetic saturation produces destructive effects on performances of AC machines. The most effects are noise, increased losses and reduced insulation life [7]- [12]. In addition, the magnetic saturation causes the variation of machine inductances in terms of magnetizing current.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the magnetic saturation produces destructive effects on performances of AC machines. The most effects are noise, increased losses and reduced insulation life [7]- [12]. In addition, the magnetic saturation causes the variation of machine inductances in terms of magnetizing current.…”
Section: Introductionmentioning
confidence: 99%